1995
DOI: 10.1016/0009-9236(95)90151-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CYP2D6 gene duplication and its repercussion on the oxidative phenotype in a white population*

Abstract: The occurrence of multiple copies of the CYP2D6 gene was investigated 217 white healthy Spaniards by the combined use of Xba I and Eco RI restriction fragment length polymorphism (RFLP) analyses. About 3.5% of the alleles yielded an 12.1 kb Eco RI-RFLP product in combination with the 42 kb Xba I-RFLP product, which is indicative of multiple CYP2D6. The prevalence of subjects carrying multiple CYP2D6 was 7%. The 12.1 kb Eco RI-RFLP product was highly associated (60%) with the presence of the genotype 29wt/42wt,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(58 citation statements)
references
References 19 publications
5
48
0
5
Order By: Relevance
“…Of the 360 volunteers, 30 (8.3%) were found to carry a duplicated functional CYP2D6 gene and were thus classified as UM. The results indicate that the prevalence of this allelic variant in the Southern Italian (Sicilian) population is similar to that in a Spanish population [22,23] . This is consistent with the more frequent distribution of CYP2D6 gene duplication in the Mediterranean area compared to Northern Europe and may be indicative of a north-south gradient of the frequency within Europe.…”
Section: Cyp2c9 Cyp2c19 and Cyp2d6supporting
confidence: 64%
“…Of the 360 volunteers, 30 (8.3%) were found to carry a duplicated functional CYP2D6 gene and were thus classified as UM. The results indicate that the prevalence of this allelic variant in the Southern Italian (Sicilian) population is similar to that in a Spanish population [22,23] . This is consistent with the more frequent distribution of CYP2D6 gene duplication in the Mediterranean area compared to Northern Europe and may be indicative of a north-south gradient of the frequency within Europe.…”
Section: Cyp2c9 Cyp2c19 and Cyp2d6supporting
confidence: 64%
“…In addition, a intake of a single dose of the probe drugs debrisoquine or 42 kb XbaI allele with two copies of the CYP2D6 gene as well sparteine with subsequent determination of the ratio between as one copy of each of the pseudogenes CYP2D8 and the urinary recovery of the drug and the metabolite. In Cau-CYP2D7 has been described [12][13][14]. The duplicated casian populations, there is a large variation in the metabolic CYP2D6 genes are usually functional, and the 42 kb allele ratio (MR) of the probe drugs, leading to the classification of has therefore been associated with the UM phenotype.…”
Section: Abstract Up To 7% Of Caucasians May Demonstrate Ultrarapidmentioning
confidence: 99%
“…Here we describe the Up to 7% of Caucasians are ultrarapid metabolizers (UMs) genomic organization of the duplicated CYP2D6 genes in the 42 of debrisoquine due to inheritance of alleles with duplication kbXbalallele. We postulate that this duplication originates from of functional CYP2D6 genes [12][13][14]. The mechanism by a homologous, unequal cross-over event which involved two 29 kb which this duplication has occurred is not known.…”
mentioning
confidence: 99%
“…Recent results from several laboratories have demonstrated that a limited CYP2D6 allele set may predict the vast majority of Caucasian individuals lacking CYP2D6 enzyme activity with close to 100% accuracy (2)(3)(4)(5)(6)(7)(8). As more CYP2D6 null and reduced activity alleles have been discovered in various populations, the ability to account for more subtle variations in CYP2D6 enzyme activity has improved.…”
mentioning
confidence: 99%